Enhanced preoperative planning in congenital polydactyly: superior assessment of MCP/MTP joint angular deformity with 3D-FS-FSPGR MRI compared to conventional radiography - Li, Jie; Yun, Quan; Jia, Yingyu; Long, Jiangtao; Wang, Qianqian; Yang, Yuankai; Xu, Shuming (Frontiers in Pediatrics, 2026)
PurposePrecise quantification of angular deformity at the metacarpophalangeal (MCP) or metatarsophalangeal (MTP) joint is paramount in congenital polydactyly surgery. It dictates the surgical center point and informs the necessity for corrective osteotomy. Conventional radiography (x-ray), while standard, suffers from inherent limitations in visualizing cartilage and soft tissue, compromising surgical planning. This study evaluates the clinical feasibility and superiority of a three-dimensional fat suppression rapid phase shifting gradient echo (3D-FS-FSPGR) magnetic resonance imaging (MRI) sequence for overcoming these limitations and achieving accurate preoperative angular assessment.MethodsPediatric patients presenting with congenital polydactyly of the hands or feet underwent preoperative imaging with both standard x-ray and the 3D-FS-FSPGR MRI sequence. Evaluation focused on characterizing angular deformities at the affected joints. Direct comparative analysis assessed the visualization of osseous alignment, cartilage architecture, joint bifurcation planes, and surrounding soft tissues, alongside the accuracy of angular measurements derived from each modality.ResultsCompared to x-ray, the 3D-FS-FSPGR MRI sequence demonstrated superior visualization of cartilage morphology, joint capsule anatomy, soft tissue, and articular surfaces at the MCP/MTP joints. This anatomical delineation translated to more accurate and reliable quantification of angular deformities. Crucially, significant discrepancies in measured joint angles were observed between MRI and x-ray. These differences are pronounced in cases where the morphology of the cartilage affects joint alignment and the complex branching planes.ConclusionConventional x-ray assessment in congenital polydactyly is limited in visualizing soft tissue and cartilage structures. The 3D-FS-FSPGR MRI sequence offers superior characterization of cartilaginous and soft tissue components, enabling more precise measurement of joint angular deformities. Its integration into the preoperative evaluation protocol demonstrates substantial clinical feasibility and tangible potential to optimize surgical site and reduce the incidence of postoperative deformities and functional impairment, thereby improving the long-term functional and aesthetic outcomes for these children.